Pandemic's influence on parents' attitudes and behaviors toward meningococcal vaccination - Litjen (L.J); Marco Aurelio P. Safadi; Michael Horn; Cristina Regojo Balboa; Elena Moya; Jamie Schanbaum; Pedro Pimenta; Emma Lambert; Lamine Soumahoro; Woo-Yun Sohn; Teresa Bruce; Yara Ruiz García (Taylor & Francis Group, 2023)
Invasive meningococcal disease is a life-threatening infection preventable through vaccination. Pediatric vaccination rates have declined during the coronavirus disease 2019 (COVID-19) pandemic. This survey aimed to understand how parents' attitudes and behaviors have changed during the pandemic with regard to immunization and, more specifically, meningococcal vaccination. An online survey was emailed to parents of eligible children 0-4 years, following the selection process from UK, France, Germany, Italy, Brazil, Argentina, and Australia; and of adolescents 11-18 years from US. Data collection took place 19 January-16 February 2021. Quotas were set to ensure a representative sample. Eleven questions relating to general perceptions around vaccination and attitudes and behaviors toward meningitis vaccination were displayed. On 4,962 parents (average 35 years) participating in the survey, most (83%) believed important for their child to continue receiving recommended vaccines during the COVID-19 pandemic. Nearly half of routine vaccine appointments were delayed or canceled due to the pandemic, and 61% of respondents were likely to have their children catch up once COVID-19 restrictions were lifted. 30% of meningitidis vaccination appointments were canceled or delayed during the pandemic, and 21% of parents did not intend to reschedule them because of lockdown/stay at home regulations, and fear of catching COVID-19 in public places. It is crucial to communicate clear instructions to health workers and the general population and to provide appropriate safety precautions in vaccination centers. This will help to maintain vaccination rates and limit infections to prevent future outbreaks.